Development of a Simple and Rapid Field Test for Monitoring Bacteriological Quality of Water - Bhutra, M.K.; Soni, Ambica (Asian Journal of Chemistry, 2016)
A rapid method for examination of faecal coliforms in water using a new chemically well defined culture medium (BS medium I & II) stable under extreme climatic conditions of desert is described. The presumptive test requiring 3 to 12 h incubation at 44°C for faecal contamination is qualitative, quicker and simpler than existing standard methods. The confirmative test for faecal coliforms (Escherichia coli) on agar plates using BS agar (II) requires incubation for another 8–10 h at 40°C. An attempt has also been made to evaluate the efficiency of BS medium for the detection of faecal as well as non-faecal origin in 18 h. It was observed that BS medium could be used for rapid isolation of coliforms even under the field conditions (37°C) with greater efficiency than the conventional media used in standard methods. The technique using new culture medium could be a good supplement to the existing methods in health centres towars control of water borne diseases like typhoid, cholera and dysentery.